Transitioning to a circular economy: A framework of economic analysis and measures of circularity - Ahmed Chennak; Konstantinos Giannakas; Tala Awada (Journal of Cleaner Production, 2026)

Bromus inermis forage production and quality under long-term rotational grazing and nutrient enrichment in Eastern Nebraska, U.S. - Hassan Shehab; Makki Khorchani; Anastasios Mazis; Jeremy Hiller; Galen Erickson; Marty Schmer; Brian Wardlow; Andy Suyker; Xiangmin Sun; Lidong Li; Rebecca McDermott; Ariel Freidenreich; et al. (Agriculture, Ecosystems & Environment, 2026)

Addressing key issues and knowledge gaps in resilience science for agriculture - Shana M. Sundstrom; Tala Awada; Elena M. Bennett; Brandon Bestelmeyer; Jennifer Hodbod; Anna Pacheco; Sheri Spiegal; Craig R. Allen (Agricultural Systems, 2025)

Flame weeding in soybean: crop tolerance confirmed during flowering stage - Luka Milosevic; Tala Awada; Amit J. Jhala; George Gogos; Sam E. Wortman; Stevan Z. Knezevic (Organic Agriculture, 2025)

Global Greenhouse Gas Emissions From Agriculture: Pathways to Sustainable Reductions - Lidong Li; Tala Awada; Yeyin Shi; Virginia L. Jin; Michael Kaiser (Global Change Biology, 2025)
Agriculture serves as both a source and a sink of global greenhouse gases (GHGs), with agricultural intensification continuing to contribute to GHG emissions. Climate‐smart agriculture, encompassing both nature‐ and technology‐based actions, offers promising solutions to mitigate GHG emissions. We synthesized global data, between 1990 and 2021, from the Food and Agriculture Organization (FAO) of the United Nations to analyze the impacts of agricultural activities on global GHG emissions from agricultural land, using structural equation modeling. We then obtained predictive estimates of agricultural GHG emissions for the future period of 2022–2050 using deep‐learning models. The FAO data show that, from 1990 to 2021, global livestock numbers, inorganic nitrogen (N) fertilizer use, crop residue, and irrigation area increased by 27%, 47%, 49%, and 37%, respectively. The increased livestock numbers contributed to the increases in CH 4 and N 2 O emissions, while inorganic N fertilizer, crop residue, and irrigation mainly contributed to the increases in N 2 O emissions. Emissions of CO 2 decreased because of a 29% reduction in net forest loss. As a result of the reduced deforestation emissions, the overall agricultural GHG emissions declined from 11.50 to 10.89 GtCO 2 eq from 1990 to 2021 despite the increases in livestock numbers, inorganic N fertilizer, crop residue, and irrigation. Looking ahead, our model predicts that if current agricultural trends persist, GHG emissions will rise to 11.82 ± 0.07 GtCO 2 eq in 2050. However, maintaining agricultural GHG emissions at the 2021 level through 2050 is possible if the rate of reduction in net forest loss is doubled. Furthermore, if the rate is tripled, agricultural GHG emissions can be limited to 9.85 ± 0.07 GtCO 2 eq in 2050. Our findings suggest that reductions in agricultural GHG emissions, alongside sustainable agricultural intensification and climate‐smart agricultural practices, can be achieved through parallel efforts emphasizing accelerated forest conservation.

On the Economics of the Transition to a Circular Economy - Ahmed Chennak; Konstantinos Giannakas; Tala Awada (Circular Economy and Sustainability, 2024)
Humanity is facing complex challenges posed by population growth, climate change, and the need to increase food, feed, fiber, and bioenergy production while confronting the scarcity of natural resources. The transition to a circular economy, characterized by reduced resource use and waste, is being increasingly recognized in academic, business, and policy making circles as essential to meeting these challenges, with the emphasis being on the development of methods and processes that enable and facilitate the transition from a linear to a circular economy. This paper argues the need for an increased emphasis on the economics of the circular economy and presents a general framework that illustrates the transition from a linear to a circular economic system. In addition, the paper highlights the economic issues that arise during the transition to increased circularity and the policy options available to facilitate the successful transition to a more circular economic system.

Global Land Use Change and Its Impact on Greenhouse Gas Emissions - Lidong Li; Tala Awada; Yao Zhang; Keith Paustian (Global Change Biology, 2024)
Anthropogenic activities have altered approximately two‐thirds of the Earth's land surface. Urbanization, industrialization, agricultural expansion, and deforestation are increasingly impacting the terrestrial landscapes, leading to shifts of areas in artificial surface (i.e., humanmade), cropland, pasture, forest, and barren land. Land use patterns and associated greenhouse gas (GHG) emissions play a critical role in global climate change. Here we synthesized 29 years of global historical data and demonstrated how land use impacts global GHG emissions using structural equation modeling. We then obtained predictive estimates of future global GHG emissions using a deep learning model. Our results show that, from 1992 to 2020, the global terrestrial areas covered by artificial surface and cropland have expanded by 133% and 6% because of population growth and socioeconomic development, resulting in 4.0% and 3.8% of declines in pasture and forest areas, respectively. Land use was significantly associated with GHG emissions ( p 2 eq from 1992 to 2020. Looking ahead, if current trends in global land use continue at the same rates, our model projects that global GHG emissions will reach 76 ± 8 GtCO 2 eq in 2050. In contrast, reducing the rates of land use change by half could limit global GHG emissions to 60 ± 3 GtCO 2 eq in 2050. Monitoring and analyzing these projections allow a better understanding of the potential impacts of various land use scenarios on global climate and planning for a sustainable future.

High-throughput physiological phenotyping of crop evapotranspiration at the plot scale - Geng (Frank) Bai; Burdette Barker; David Scoby; Suat Irmak; Joe D. Luck; Christopher M.U. Neale; James C. Schnable; Tala Awada; William P. Kustas; Yufeng Ge (Field Crops Research, 2024)

Machine Learning for Modeling Soil Organic Carbon as Affected by Land Cover Change in the Nebraska Sandhills, USA - Lidong Li; Wanwan Liang; Tala Awada; Jeremy Hiller; Michael Kaiser (Environmental Modeling & Assessment, 2024)

Conversion of native grassland to coniferous forests decreased stocks of soil organic carbon and microbial biomass - Lidong Li; Elnaz Hosseiniaghdam; Rhae Drijber; Elizabeth Jeske; Tala Awada; Jeremy Hiller; Michael Kaiser (Plant and Soil, 2023)
Aims Encroachment of woody species into grasslands is a global phenomenon that affects ecosystem services, including soil organic carbon (SOC) storage and microbial community structure. We determined stocks of SOC and soil microbial biomass as affected by conversion of grasslands to coniferous forests. Methods We examined SOC and soil δ 13 C signatures under three vegetation covers: native grasslands, eastern redcedar ( Juniperus virginiana ), and ponderosa pine ( Pinus ponderosa ), at six soil depths (0 − 10, 10 − 30, 30 − 100, 100 − 170, 170 − 240, 240 − 300 cm). Fatty acid methyl esters (FAMEs) were used to quantify soil microbial biomass (MB) and as biomarkers for bacteria, arbuscular mycorrhizal fungi (AMF), and saprophytic fungi (SF) which includes ectomycorrhizal fungi (ECM). Results Native grasslands had higher overall SOC and MB stocks in the top 300 cm soil depth (7.39 kg SOC m − 2 and 65.6 mmol MB m − 2 ) than converted cedar (6.80 kg SOC m − 2 and 38.4 mmol MB m − 2 ) or pine (5.87 kg SOC m − 2 and 39.9 mmol MB m − 2 ) forest. Losses of AMF biomass occurred on conversion of native grasslands to pine forest. Stocks of SF biomass only differed with vegetation type in topsoil. Conclusions Conversion of native grasslands to cedar or pine forest increased topsoil (0 − 10 cm) SOC storage due to needle litter accumulation. Conversion of native grasslands to forests decreased subsoil (10 − 300 cm) SOC stocks and had replaced, by increasing depth, 30 to 19% and 45 to 26% of grassland C with cedar and pine C, respectively. Changes in soil pH, nutrients, and soil microbial communities accelerated SOC turnover.

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

Determining factors that impact the calibration of consumer-grade digital cameras used for vegetation analysis - Anthony L. Nguy-Robertson; Emma M. Brinley Buckley; Andrew S. Suyker; Tala N. Awada (International Journal of Remote Sensing, 2016)

Expression of Chlorovirus MT325 aquaglyceroporin (aqpv1) in tobacco and its role in mitigating drought stress - Saadia Bihmidine; Mingxia Cao; Ming Kang; Tala Awada; James L. Van Etten; David D. Dunigan; Tom E. Clemente (Planta, 2014)

Activity of the Arabidopsis RD29A and RD29B promoter elements in soybean under water stress - Saadia Bihmidine; Jiusheng Lin; Julie M. Stone; Tala Awada; James E. Specht; Tom E. Clemente (Planta, 2013)

Effects of Grazing Exclusion on Soil Properties and on Ecosystem Carbon and Nitrogen Storage in a Sandy Rangeland of Inner Mongolia, Northern China - Yinping Chen; Yuqiang Li; Xueyong Zhao; Tala Awada; Wen Shang; Juanjuan Han (Environmental Management, 2012)

Characterization of abiotic stress-responsive Arabidopsis thaliana RD29A and RD29B genes and evaluation of transgenes - Joseph Msanne; Jiusheng Lin; Julie M. Stone; Tala Awada (Planta, 2011)